Effect of Boric Acid on Fertility, Aggressiveness and Sex Behaviour in Male Rats - Nusier, Mohamad; Bataineh, H.N. (Asian Journal of Chemistry, 2016)
The aim of this research was to investigate the effects of long-term ingestion of boric acid on fertility, aggressiveness and sexual behaviour in Sprague-Dawley male rats. The study was conducted in the Animal House Unit at Jordan University of Science and Technology, School of Medicine during the period September 2002 to January 2003. The control group (n = 10) received powdered feed with no additives and the treated group (n = 10) received powdered feed containing 9000 ppm (w/w) boric acid for 60 days. After 24 h of the last dose, the animals were weighed and autopsied under light ether anesthesia. The blood was collected for serum studies. Fertility was estimated in both groups. Sperm was tested for motility and counted. Initial and final body weights were recorded. Reproductive tract organs were also weighed. Histological and histometry studies were performed on reproductive organs (testes, epididymides, seminal vesicle, ventral prostate and vas deferens) as well as on liver, kidney and heart muscle. Testicular cell population was counted. Total protein, cholesterol, triglycerides, serum aspartate aminotranferase, serum alanine aminotranferase, plasma FSH and testosterone concentrations were measured. Aggressiveness and sex behaviorus were investigated. Data was expressed as mean ± standard deviation.